2016
DOI: 10.3390/ijms17111933
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression Analysis of Polygalacturonase Family Members during Peach Fruit Softening

Abstract: Polygalacturonase (PG) is an important hydrolytic enzyme involved in pectin degradation during fruit softening. However, the roles of PG family members in fruit softening remain unclear. We identified 45 PpPG genes in the peach genome which are clustered into six subclasses. PpPGs consist of four to nine exons and three to eight introns, and the exon/intron structure is basically conserved in all but subclass E. Only 16 PpPG genes were expressed in ripening fruit, and their expression profiles were analyzed du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 62 publications
(95 reference statements)
4
46
0
Order By: Relevance
“…Putative gene function identification was retrieved from Genome Database for Rosaceae (GDR; ftp://ftp.bioinfo.wsu.edu/species/Prunus_persica), from Phytozome v12, and from the literature (De Franceschi et al , Song et al , Huan et al , , Qian et al , Guo et al ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Putative gene function identification was retrieved from Genome Database for Rosaceae (GDR; ftp://ftp.bioinfo.wsu.edu/species/Prunus_persica), from Phytozome v12, and from the literature (De Franceschi et al , Song et al , Huan et al , , Qian et al , Guo et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Redundant GO terms were removed using REVIGO (Supek et al 2011), with the following parameters: Allowed similarity: small; GO categories associated to: P-values; GO term sizes database: A. thaliana; semantic similarity measure to use: SimRel. and from the literature (De Franceschi et al 2013, Song et al 2014, Huan et al 2016a, 2016b, Qian et al 2016, Guo et al 2017.…”
Section: Functional Enrichment Analysismentioning
confidence: 99%
“…Many studies have reported that the process of fruit softening is related to cell wall modifications involving depolymerization of pectins and matrix glycans, solubilization of pectin polymers, and the loss of neutral sugars from pectin side chains ( Ruiz May and Rose, 2013 ; Tucker, 2014 ; Paniagua et al, 2016 ). Enzymes related to cell wall modifications that potentially play a role in fruit softening include polygalacturonase (PG; EC3.2.1.15), pectin methylesterases (PME; EC3.1.1.11), β-galactosidase (β-gal; EC3.2.1.23), cellulase (EC3.2.1.4), and xyloglucan endotransglycosylase (EC2.4.1.207) ( Hinton and Pressey, 1974 ; Lazan et al, 2004 ; Belleau-Deytieux et al, 2009 ; Qian et al, 2016 ). β-Gal increases cell wall porosity by depolymerizing galactose side chains of xyloglucan, rhamnogalacturonan I, and hemicelluloses, which allows binding of PG, PME, or other cell wall hydrolases to pectin; consequently accelerating fruit softening ( Brummell and Harpster, 2001 ; Gerardi et al, 2012 ; Pose et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Processes triggered in the mature fruit would be directed to glycogen and isocitrate metabolism, and protein localization ( Figure 3B), whereas a manual inspection indicated that protein-driven cell wall modi cation was much more represented in ripe fruit than in mature fruit (nine versus two proteins, Table 1, Figure 4B). Seven of these cell wall proteins have been experimentally shown to be ethylene responsive: polygalacturonase (PG) Prupe.2G300900 [44], PpPG21 (Prupe.4G261900) [44], PpPG22 (Prupe.4G262200) [14,44,45], beta-galactosidase (Prupe.3G050200) [14], pectin methylesterase inhibitor (Prupe.1G114500) [46], expansin 3 (Prupe.6G075100) [45], and endo-1,4-beta-glucanase PpEG1 (Prupe.5G131300) [47], in according to the increase in ethylene production at ripe stage [28] highlighting its relevance as a ripening promoting hormone in melting peach fruit varieties. In addition, protein-coding genes from PpEG1, PpPG21, Prupe.2G300900 and Prupe.3G050200 (PpBGAL2) belonged to the same gene cluster with higher expression in ripe fruit compared to mature fruit, in the white esh fast-melting peach "Hu Jing Mi Lu" (HJ) [48], pointing to a conserved mechanism of cell wall dismantling in peach fruits with a different genetic background.…”
Section: Discussionmentioning
confidence: 99%